2022
DOI: 10.1515/ntrev-2022-0104
|View full text |Cite
|
Sign up to set email alerts
|

A brief review of nanoparticles-doped PEDOT:PSS nanocomposite for OLED and OPV

Abstract: In recent years, several strategies have been proposed and demonstrated to enhance the efficiency of organic light-emitting diodes (OLEDs) and organic photovoltaics (OPVs). In both types of devices, poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is commonly used to enhance hole injection. The layer is further designed by incorporating metallic-based, carbon-based, organic, inorganic, and hybrid nanoparticles with the aim of improving the performance and hence the efficiency through the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…One of the most effective methods is the introduction of the doping additives into the aqueous dispersion of PEDOT:PSS. [ 19 ] Various materials have been used and reported such as organic solvents, surfactants, acids, metal particles, as well as quantum dots (QDs). [ 20–23 ] For example, Li et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most effective methods is the introduction of the doping additives into the aqueous dispersion of PEDOT:PSS. [ 19 ] Various materials have been used and reported such as organic solvents, surfactants, acids, metal particles, as well as quantum dots (QDs). [ 20–23 ] For example, Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most effective methods is the introduction of the doping additives into the aqueous dispersion of PEDOT:PSS. [19] Various materials have been used and reported such as organic solvents, surfactants, acids, metal particles, as well as quantum dots (QDs). [20][21][22][23] For example, Li et al demonstrated a new method using deionized water dip-rinse to remove additional hydrophilic PSS, while conductive PEDOT remain on functional PSS, thus improving the conductivity and morphology of PEDOT:PSS film.…”
Section: Introductionmentioning
confidence: 99%
“…Poly (3,4-ethylenedioxythiphene):poly(styrenesulfonate) (PEDOT:PSS) has been widely used in electrical or electro-optical devices, such as light-emitting diodes, sensors, and solar cells [1][2][3][4][5], owing to its environmental friendliness, high conductivity, and ease of fabrication. However, the conductivity of PEDOT:PSS is not suitable for film-based fabrication because the PEDOT:PSS consists of the PEDOT conductor and PSS insulator.…”
Section: Introductionmentioning
confidence: 99%
“…Organic light-emitting diodes (OLEDs) have become a popular option for display and lighting applications because their high efficiency, slim profile, lightweight design, and ability to be manufactured on flexible substrates in addition to their exceptional colour contrast and brightness [1][2][3][4] . However, conventional OLEDs suffer from an optical loss of approximately 80%, whereby the majority of the emitted light is trapped inside the OLED device.…”
Section: Introductionmentioning
confidence: 99%